Successful Hematopoietic Stem Cell Transplantation Following a Cyclophosphamide-Containing Preparative Regimen with Concomitant Phenobarbital Administration. (11th October 2012) - Weber, Catherine; Kasberg, Heather; Copelan, Edward
Abstract : Cyclophosphamide is an immunosuppressive agent and an anticancer prodrug which requires bioactivation catalyzed primarily by cytochrome P450 enzymes in order to be transformed into its active alkylating compounds. Concomitant administration of drugs known to inhibit or induce this enzyme system is a clinical concern. Herein, we present the case of a chronically ill 21-year-old patient who received high-dose cyclophosphamide, equine antithymocyte globulin (eATG), and total body irradiation (TBI) followed by an allogeneic hematopoietic stem cell transplant (HSCT) for severe aplastic anemia. Throughout her hospitalization, she continued to receive quadruple anticonvulsant therapy including phenobarbital for her long-standing seizure history. The preparative regimen was tolerated well aside from a hypersensitivity reaction to eATG, and minimal cyclophosphamide-related toxicities. Safe and effective administration of high-dose cyclophosphamide was possible with multidisciplinary care consisting of physician, nursing, pharmacy, neurology consultation, as well as social work and case management.